Erosion and environment - Holy, Milos (Environmental sciences and applications, 1984)
Erosion and Environment focuses on the disturbance of the natural soil cover that exposes the soil surface to the action of erosion agents such as the destructive effects of water and wind. The topics discussed in this book include the effects of erosion on the national economy; classification of erosion; mechanism of erosion processes; theory of water erosion; and predicting intensity of water erosion and modeling erosion processes. The theory of wind erosion; intensity of wind erosion and predicting wind erosion; erosion and environmental control; and economics of erosion control are also el.